Defining French ‘Romanesque’: the Zodiaque series - Janet T. Marquardt (Journal of Art Historiography, 2009)
This essay examines the use of the term “Romanesque” as an artistic style and time period for architecture, sculpture and other arts photographed and published in a journal and multiple series of books by monks at the abbey of la Pierre-qui-Vire in Burgundy between 1951 and 2001. Although the term suggests a coherent body of work with related qualities, the actual imagery destabilizes our understanding of how one can actually define Romanesque. At the same time, the artfully composed photogravure illustrations and inclusive survey of sites strongly influenced art historians of the twentieth century by reinforcing notions of geographic workshops, bringing a fresh, modernist aesthetic to well known material, and publishing photographs of many unknown works for the first time.